A formação dos elementos químicos: astronomia contextualizando a Tabela Periódica - Pinho, Janildes Silva (2024)
The Periodic Table is an essential pedagogical tool for understanding various concepts covered in the Chemistry discipline. However, it is observed that the teaching of this content prioritizes the conceptual through memorization, which does not contribute to student engagement during classes. Faced with this scenario, using a pedagogical intervention type research, this work aimed to relate Astronomy and Chemistry through an interdisciplinary approach and contextualized in the Periodic Table and, in this way, promote a more dynamic and motivating teaching, enabling the active construction of knowledge. The theme chosen to make this relationship is the Origin of Chemical Elements, through the study of the atom, primordial nucleosynthesis (Big Bang), stellar nucleosynthesis and cosmic rays. For this purpose, practical interventions were developed aiming at problematizing and investigative teaching, in order to contribute to the formation of students' critical and scientific sense. The actions were carried out at State School José Ferreira Pinto, in the city of Feira de Santana-Ba, with 1st year high school classes. The educational products generated by this work consist of a didactic sequence entitled “Origin of Chemical Elements: Astronomy and Periodic Table” and the board game “Cosmic Trail”, together with support material formed by the didactic kit “Quarks: Understanding the Constitution of Matter". The results of the pedagogical intervention, based on a qualitative analysis, showed greater student participation in Chemistry classes, as well as the appropriation of vocabulary and content relating to the topic of Formation of Chemical Elements, relating it to the Periodic Table.